The corn of plenty - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Pioneer Hi-bred International in Zimbabwe has developed two new maize varieties able to fight off the feared grey leaf spot disease. Tests by both smallholder and large-scale farmers show these varieties as high yielding (9 11 t/ha), suitable for...